2010
DOI: 10.1007/s10439-010-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Microscopy Analyses to Determine Good vs. Failed Tissue Engineered Oral Mucosa Under Normal or Thermally Stressed Culture Conditions

Abstract: This study uses scanning acoustic microscopy (SAM) ultrasonic profilometry to determine acceptable vs. failed tissue engineered oral mucosa. Specifically, ex vivo-produced oral mucosal equivalents (EVPOMEs) under normal or thermally stressed culture conditions were scanned with the SAM operator blinded to the culture conditions. As seeded cells proliferate, they fill in and smooth out the surface irregularities; they then stratify and produce a keratinized protective upper layer. Some of these transformations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Diminished cyclic variation may perhaps depend on less change in sound speed during a cardiac cycle because of incomeplete protein content of myocytes. Recently, several researchers have focused on sound speed of living cells and sought to utilize this technology in several clinical fields including in vivo tissues and cultured cells [31][32][33]. If modern technology allows development of the acoustic microscope system for use in a catheter-based system such as intracardiac ultrasound, new knowledge may be obtained regarding cyclic variation of myocyte sound speed, leading to diagnosis of genetic cardiomyopathy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Diminished cyclic variation may perhaps depend on less change in sound speed during a cardiac cycle because of incomeplete protein content of myocytes. Recently, several researchers have focused on sound speed of living cells and sought to utilize this technology in several clinical fields including in vivo tissues and cultured cells [31][32][33]. If modern technology allows development of the acoustic microscope system for use in a catheter-based system such as intracardiac ultrasound, new knowledge may be obtained regarding cyclic variation of myocyte sound speed, leading to diagnosis of genetic cardiomyopathy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…18 Acoustic microscopy techniques (at 61 MHz), have been used to characterize the development and surface irregularities of engineered human oral mucosal constructs. 19,20 …”
Section: B-mode Ultrasound Imagingmentioning
confidence: 99%
“…LIPUS has proven to be a clinically established, widely used and FDA approved therapy to enhance bone growth during healing of non-union fractures and other osseous defects (32, 33). Various studies have also shown that ultrasound can control the rate of scaffold degradation (13, 34-35-36), improve scaffold integration, and that they modulate different specific cellular aspects (14, 29, 37-38-39-40-41-42). Recently, our group demonstrated that LIPUS with spatial averaged and temporal averaged (SATA) intensity of 30 mW/cm 2 is able (i) to maintain hMSCs stemness in vitro for up to 28 days and therefore guarantee the presence of a stem cells reservoir and (ii) to enhance and accelerate the osteogenic differentiation of hMSCs, thereby inducing the release of a master regulator of the angiogenic process (VEGF) (unpublished data).…”
Section: Introductionmentioning
confidence: 99%